Milk Quality and Prolactin Hormone Levels of Murrah Buffalo Fed with Local Forage and Urea Molasses Block at Kapau Village Agam Regency West Sumatra - Roza, Elly; Aritonang, Salam N.; Yellita, Yulia; Susanty, Hilda; Rizqan (Journal of Buffalo Science, 2025)
Feeding is one of the main factors in the success of a Murrah buffalo farming business. Good quality feed will increase Murrah buffalo’s productivity, including the quality of milk produced. Buffalo (Bubalus bubalis) milk has the advantage of 6-8% fat and 3-8% protein compared to 3-4% fat and protein content in cow’s (Bos taurus) milk. This study aims to improve milk quality and prolactin hormone levels in Murrah buffaloes by providing local forage-based feed and urea molasses block. This research is an experimental study with a Latin Square Design (LSD), using four female Murrah buffaloes as the research sample with the following feeding: P1 = basal feed (10% of body weight); P2 = 30% sweet potato leaves + 30% cassava leaves + 40% P1 + urea molasses block; P3 = 40% sweet potato leaves + 40% cassava leaves + 20% P1 + urea molasses block; P4 = 50% sweet potato leaves + 50% cassava leaves + urea molasses block. The parameters measured in this study were protein, amino acids, fat, milk fatty acids, and Murrah buffalo Prolactin Hormone levels. The results obtained in the study in order are as follows: protein (2.37-3.83%); amino acids (2.54-8.45%w/w); fat (5.86-9.22%); prolactin (1.61-1.99ng/ml). The results showed that feeding 50% sweet potato leaves, 50% cassava leaves, and urea molasses block can improve milk quality and prolactin hormone levels in Murrah buffaloes.